Perancangan dan Implementasi ISO 9001:2008 di PT. Bondi Syad Mulia, Surabaya. - Perdana, Bayu; Rahardjo, Jani (Jurnal Titra, 2013)
PT. Bondi Syad Mulia plans to conduct ISO 9001:2008 certification. ISO 9001:2008 is an international standard governing the quality management system in manufacturing and services industry. Companyâs management system is expected to become more structured with the application of ISO 9001:2008. A quality management system design is based on the clauses of ISO 9001:2008. The goal of this design is implementing a quality management system and obtaining ISO 9001:2008 certifications. Gap analysis is conducted todetermine whether the requirements of ISO 9001:2008 have been fulfilled or not. The results indicated that only 34.55% requirements in ISO 9001:2008 have been fulfilled in the company. It is indicated that the company needs to redesign a quality management system, which including quality manual and quality procedures of the company. The implementation of the new design is done after all of the new designs have been approved by the top management. After the implementation, an evaluation process is done through audits and management reviews. The results of the final gap analysis indicated that the necessary requirements in ISO 9001:2008 have been fulfilled 100% and the company is ready for the certification process.